Agricultural Economics Current Issues - Kulshreshtha, Surendra N. (IntechOpen, 2019)
Agricultural Economics - Current Issues is a review of topics related to the economics of agriculture in various parts of the world. It contains a total of seven chapters. These contributions are related to some of the significant current problems facing these regions. The book is divided into four parts. The first part is simply an introduction to the field of agricultural economics. It charts the development of the field from its origin of farm management economics to the current state of a variety of subjects in various parts of the world. In the second section, an issue related to marketing is discussed. This is followed in the third section by an issue related to water resource economics. In the last section the remaining three chapters are devoted to agricultural environment-related topics. All chapters present guidance for policymaking.